2016
DOI: 10.3389/fgene.2016.00056
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes: The Link between GPCR Activation and Metastatic Potential?

Abstract: The activation of G-Protein Coupled Receptors (GPCRs) by their respective ligands initiates a cascade of multiple signaling processes within the cell, regulating growth, metabolism and other essential cellular functions. Dysregulation and aberrant expression of these GPCRs and their subsequent signaling cascades are associated with many different types of pathologies, including cancer. The main life threatening complication in patients diagnosed with cancer is the dissemination of cells from the primary tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 152 publications
1
19
0
Order By: Relevance
“…Receptor target modelling (MetaCore data-mining and pathway analysis, Thomson Reuters) of the 31 unique HiMet-C6 proteins in the list revealed that 21/31 of the proteins (67.7%) are involved in G-protein coupled receptor signaling events (GO Processes) (Figure 6) known to play critical roles in tumor growth and metastasis [37]. More recently, a link between GPCR signaling, extracellular vesicles and metastasis has been published [38]. …”
Section: Resultsmentioning
confidence: 99%
“…Receptor target modelling (MetaCore data-mining and pathway analysis, Thomson Reuters) of the 31 unique HiMet-C6 proteins in the list revealed that 21/31 of the proteins (67.7%) are involved in G-protein coupled receptor signaling events (GO Processes) (Figure 6) known to play critical roles in tumor growth and metastasis [37]. More recently, a link between GPCR signaling, extracellular vesicles and metastasis has been published [38]. …”
Section: Resultsmentioning
confidence: 99%
“…The function of lipid rafts was invoked in facilitating GPCR activation by these lipids. However, only a few studies have investigated if EVs or exosomes exchange GPCRs between cells (Isola & Chen, 2016; Ye et al, 2002). Recently, ectosomes, EVs budding off cilia, were reported to accumulate GPCRs, but a role of ectosome-bound GPCRs in cancer has not been described yet (Isola & Chen, 2016; Nager et al, 2017; Soetedjo & Jin, 2014).…”
Section: Exosomes In Cancer: Target Tissue Biohacking and Hijacking Omentioning
confidence: 99%
“…However, only a few studies have investigated if EVs or exosomes exchange GPCRs between cells (Isola & Chen, 2016; Ye et al, 2002). Recently, ectosomes, EVs budding off cilia, were reported to accumulate GPCRs, but a role of ectosome-bound GPCRs in cancer has not been described yet (Isola & Chen, 2016; Nager et al, 2017; Soetedjo & Jin, 2014). One study found that exosomes can transfer the A2A adenosine receptor (A2AR) from A2AR expressing to non-expressing cells with functional recovery of this GPCR, which suggests that exosomal transfer of receptors endows the recipient cell with the ability to respond to the same signals as the donor cell (Clayton, Al-Taei, Webber, Mason, & Tabi, 2011; Isola & Chen, 2016) (Fig.…”
Section: Exosomes In Cancer: Target Tissue Biohacking and Hijacking Omentioning
confidence: 99%
“…These newly released exosomes have the ability to travel long distances within the body, or interact with local cells. The uptake of exosomes by target cells can occur in different ways; engulfment of the exosomes by the recipient cells often by clathrin-dependent endocytosis or, under certain conditions, lipid-dependent membrane fusion [56]. …”
Section: Exosomesmentioning
confidence: 99%